Competing Controls of Effective Stress Variation and Chloritization on Friction and Stability of Faults in Granite: Implications for Seismicity Triggered by Fluid Injection. Issue 8 (17th August 2022) - Zhang, Fengshou; Huang, Rui; An, Mengke; Min, Ki‐Bok; Elsworth, Derek; Hofmann, Hannes; Wang, Xiaoguang
Abstract: Fluids injection for hydraulic stimulation and fracturing, typical in the development of enhanced geothermal systems (EGS) in granites, can reactivate deep faults and induce seismicity. Such faults typically contain chlorite coatings as an alteration product that may impact styles of deformation—aseismic through seismic. We performed low velocity shear experiments on simulated granite fault gouges under conditions typifying a geothermal reservoir at ∼4‐km depth with a confining pressure of 110 MPa, a temperature of 150°C, fluid pressures of 21–80 MPa, and chlorite contents of 0–100%, to investigate the influence of variation in effective stress and mineral composition on fault strength and stability. Our results show a transition from velocity‐strengthening to velocity‐weakening behavior in simulated granite gouge when the effective confining pressure was reduced from 89 to 30 MPa, characterized by a transition from fault compaction to dilation—as revealed by microstructural observations—with implications in enabling unstable failure. Conversely, increasing chlorite content stabilizes slip but reduces frictional strength. The microstructures of these mixed gouges exhibit shear localized on chlorite‐enriched planes and promoting fault sliding. These results suggest that earthquake ruptures occurring during fluid injection can be facilitated by effective stress variations and that both controlling fluid overpressures (effective stresses) and being aware of the presence of alteration minerals are both important controls in mitigating such injection‐induced seismic risks. Plain Language Summary: Enhanced geothermal systems (EGS) host an increasing number of induced earthquakes potentially linked to hydraulic stimulation. Rock cores recovered from geothermal reservoirs worldwide show an abundance of chlorite coatings on fault surfaces—present both natively and as a result of fluid circulation. To understand whether slip on deep fault will result in earthquakes, we measure the frictional properties of powdered granite fault rocks from the Pohang geothermal reservoir where an earthquake has occurred. We vary chlorite content and effective confining pressures and observe stable slip at higher effective confining pressures that transitions to unstable slip at lower effective confining pressures. Reducing the effective confining pressure destabilizes the fault behavior at in situ stress and temperature representative of the reservoir where an earthquake was observed. The addition of chlorite in the simulated gouge results in the opposite result, reducing the frictional strength but resulting in stable (aseismic) slip. Our results highlight the importance of effective stress variation and mineral composition in controlling fault frictional strength and stability, with their potential contributions to earthquake triggering. Key Points: Effective stress variation and chloritization exert competing controls on friction and stability of granite faults Lower effective stress accentuates velocity‐weakening behavior but retains high strength Conversely, chloritization reduces frictional strength but promotes stable failure